Asymmetric Decentralization on the Recognition of Customary Law Community Units turned Customary Villages in Indonesia - Abdurrahman Al-Fatih Ifdal; Ratih Lestarini (Faculty of Law, Universitas Pekalongan, 2023)
Transformation from a customary law community unit (kesatuan masyarakat hukum adat) in Indonesia into a customary village (desa adat) indicates a move enacted by the government of Indonesia to promote asymmetric decentralization. The problem that arises therein is the loss of self-governing community autonomy when the autonomy is combined with local self-government functions, especially when the supervision from the central government to local units in each local government becomes too excessive. As such, the study aims to examine how asymmetric decentralization affects the paradigm of recognition of government functions (local self-government) in customary law community units turned customary villages. The focus of this research is on the recognition of the Baduy tribe in Kanekes Village, Leuwidamar District, Lebak Regency, Banten Province as a customary village. The output of this research is to know the consequences of adopting asymmetric decentralization to the paradigm of local self-government in customary law community units that become customary villages.